1994
DOI: 10.1002/1096-9101(1994)14:2<178::aid-lsm1900140211>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Nd:YAG laser excision of a giant gingival pyogenic granuloma of pregnancy

Abstract: A 19-year-old Hispanic nullipara experienced the rapid growth of an oral lesion on the right lower gingiva which she had first noticed at 29 weeks gestation. The lesion interfered with oral hygiene and eating. At surgery, the lesion measured 3.5 x 2.5 x 2.0 cm. Biopsy confirmed a pyogenic granuloma ("granuloma gravidarum"). Panorex films showed no bony invasion. The lesion was excised using the Nd:YAG laser under general anesthesia when the patient had reached 36 3/7 weeks gestation. We chose the Nd:YAG laser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
6

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 14 publications
0
44
0
6
Order By: Relevance
“…[26][27][28][29] Meffert et al 30 used the flash lamp pulsed dye laser to treat a resolute intraoral mass of granulation tissue, and deduced that a series of treatments with the pulsed dye laser worked well on this lesion. Powell et al 31 reported one of the first uses of Nd:YAG laser for excision of PG, and noticed decreased risk of bleeding in comparison to other methods along with superior coagulation characteristics; which were the reasons why they chose Nd:YAG laser. Kocaman et al 8 proposed the use of Nd:YAG laser in the treatment of PG, due to its effect of decreasing bleeding during operation with a consequent reduction in operating time, promoted postoperative hemostasis and better patient acceptance.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…[26][27][28][29] Meffert et al 30 used the flash lamp pulsed dye laser to treat a resolute intraoral mass of granulation tissue, and deduced that a series of treatments with the pulsed dye laser worked well on this lesion. Powell et al 31 reported one of the first uses of Nd:YAG laser for excision of PG, and noticed decreased risk of bleeding in comparison to other methods along with superior coagulation characteristics; which were the reasons why they chose Nd:YAG laser. Kocaman et al 8 proposed the use of Nd:YAG laser in the treatment of PG, due to its effect of decreasing bleeding during operation with a consequent reduction in operating time, promoted postoperative hemostasis and better patient acceptance.…”
Section: Discussionmentioning
confidence: 91%
“…During the excision, irritant agents such as dental plaque, calculus, foreign bodies, defective restoration and source of trauma should be eliminated. 9,11 Otherwise electric cauterization, 18 cryosurgery, 19,20 sodium tetradecyl sulfate sclerotherapy, 21,22 monoethanolamine oleate ligation, absolute ethanol injection, 23 cauterization with silver nitrate, 24 intralesional steroids, 25 flash lamp pulsed dye laser, [26][27][28][29][30] neodymium-doped yttrium aluminium garnet (Nd:YAG) laser, 8,31 carbon dioxide (CO 2 ) laser, 32 erbium-doped yttrium aluminum garnet (Er:YAG) laser 9 and diode laser 2,3,33,34 have also been used by various clinicians to eliminate the lesion. Although PG does not show infiltrative tendency or malignant transformation potential, the recurrence rate after simple excision is comparatively high (about 16%); thus in some cases re-excision is required.…”
Section: Introductionmentioning
confidence: 99%
“…Operation during pregnancy is not a preferred therapy method since it shows recurrency. If there is excess bleeding an chewing disorders that disturb patients comfort and daily life surgical tretment can be taken into concideration as shown in some studies 2,17,19 . In over study we didn't consider surgical treatment because the patient stated that she did not have the complaints that we mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Powell ve ark. [7], Nd:YAG lazeri lezyonun eksizyonu için kullanmış ve düşük kanama riski ve diğer cerrahi tedavilerle uygulanabilirliği yüzünden alternatif tedavi olarak düşünmüşler. White ve ark.…”
Section: Discussionunclassified